Anastazego Synaity teologia klimatu - Gilski, Marek; Wąsek, Damian (Vox Patrum, 2024)
This article aims to answer the question of what place the climate issue has in Anastasius Sinaita’s theological reflection. It consists of two parts: the first presents the image of God emerging from the Sinaita’s analyses, while the second focuses on man’s responsibility, whose decisions are conditioned by many factors, including climate. The main conclusions include: 1. In his work Quaestiones et responsiones, Anastasius refers to climate-related issues more than twenty times. He mentions climate change, the characteristics of climates, the different types of climates and their effects on humans. 2. Life expectancy, diseases, and epidemics in the vast majority of cases are, in the view of Anastasius the Sinaite, related to climate and diet and not to morality or adherence to the correct religion. 3 Sinaitic theological reflection can be developed in at least three directions. First, it allows linking ecological issues to construct a correct image of God. Second, it sensitizes the connection between environmental devastation and human suffering, an essential area of mercy theology understood as "healing wounds." Third, it builds a broad context for the inculturation of the Church’s teaching, as it points out the role of various climatic factors on human attitudes and behaviour. Anastasius’ thought also seems to provide serious arguments for modern evolutionary theology. This is because it makes it possible to locate its crucial claim about the autonomy of the laws of nature in the ancient tradition.